Exosomes in hypoxia: generation, secretion, and physiological roles in cancer progression - Mu, Yufeng; Yang, Mengrui; Liu, Jingyang; Yao, Yan; Sun, Huimin; Zhuang, Jing (Frontiers in Immunology, 2025)
The hypoxic microenvironment represents a universal hallmark feature of most solid tumors, profoundly shaping cancer progression through multifaceted mechanisms. Acting as nanoscale molecular envoys, exosomes transport oncogenic cargoes (including non-coding RNAs, mutated proteins, and metabolites) to reprogram stromal cells, prime pre-metastatic niches, and establish tumor-host metabolic symbiosis. Their lipid bilayer architecture ensures the protection of labile hypoxia-responsive factors, positioning them as critical amplifiers of intercellular crosstalk within the tumor microenvironment. Despite significant advances, critical gaps persist in understanding the spatiotemporal regulation of exosomal release under hypoxia, particularly the organ-specific variations in hypoxic exosome signatures revealed by single-vesicle analyses. This review synthesizes recent advances in the intricate interplay between hypoxia and exosomes, emphasizing hypoxia-related signaling pathways that directly modulate exosome biogenesis and indirectly activate hypoxia-associated microenvironmental remodeling, alongside their distinct regulatory effects on exosomal cargo composition. Furthermore, it delineates the pivotal role of hypoxia-specific exosomes in driving cancer malignancy, including metastatic dissemination, immune evasion, and therapy resistance. By integrating molecular mechanisms with clinically actionable insights, this work establishes a translational framework for targeting the hypoxic exosome network in precision oncology, offering strategic references for biomarker discovery and therapeutic development.